The Poet of lron - Stein, Clare (Respectus Philologicus, 2002)
The purpose of the article The Poet of Iron by C. E. Stein is to analyse V. Chlebnikov’s poem In the Homeland of a Beautiful Death - Mashuka ... (Na rodine krasivoj smerti - Mašuke ... ) which is devoted to the Russian poet Lermontov (M. Ju. Lermontov). The text of the poem, which is clearly metapoetic, has the most complex multi-layered poetic system. The aspects of the analysis are those of linguistic poetry primarily as well as cognitive linguistics and general cultural study. The author of the article raises a hypothesis that Chlebnikov literally based his poem on many texts written by Lermontov. The text created by Chlebnikov in itself is a system of interpretation of creative writing and suggests new approaches to the research of the inheritance of Lermontov’s creative works. The author of the article outlines a hierarchy of different text-types, which is used by Vladimir Chlebnikov to build up the metapoetic text of his poem: Poetic texts by Lermontov. His poem Dagger (Kinžal) given the first priority. Paintings as Lermontov’s texts. Biographical facts and his way of life as Lermontov’s texts (sociophysical context). The name of Michael (Michail) as the quintessence of creation and the strategy of interpretation. Reference to the iconographic origin of metapoetic texts by Lermontov.